2022
DOI: 10.5267/j.msl.2021.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Subjective norms as a mediation of the opportunity to donate factors and agreeableness personality that can affect the intention to donate

Abstract: The purpose of this study was to determine the role of subjective norms as a mediation between the relationship opportunity to donate and agreeableness personality on intention to donate. This research includes a quantitative approach with a survey method distributed to 400 participants of BPJAMSOSTEK East Java Province using a Likert scale. Data analysis using SEM using WarpPLS 6.0 software. The results of this study state that subjective norms can be a link between the opportunity to donate and in accordance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…This view may also be in line with results from the Mexican sample (Study 2), which showed that agreeableness, one of the Big Five personality traits, significantly predicted the amount of participants’ donations. This is consistent with previous research that demonstrated the agreeableness-prosociality association, whereby agreeable individuals are likely to display prosocial attitudes and behaviors (e.g., Bolt et al, 2011; Carlo et al, 2005; Graziano et al, 2007; Susanto et al, 2022). On both the individual and societal levels, agreeableness (characterized with warmth, trust, courtesy, and cooperativeness) is known to be related to collectivism (Taras et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…This view may also be in line with results from the Mexican sample (Study 2), which showed that agreeableness, one of the Big Five personality traits, significantly predicted the amount of participants’ donations. This is consistent with previous research that demonstrated the agreeableness-prosociality association, whereby agreeable individuals are likely to display prosocial attitudes and behaviors (e.g., Bolt et al, 2011; Carlo et al, 2005; Graziano et al, 2007; Susanto et al, 2022). On both the individual and societal levels, agreeableness (characterized with warmth, trust, courtesy, and cooperativeness) is known to be related to collectivism (Taras et al, 2010).…”
Section: Discussionsupporting
confidence: 92%